Investigating flexible feeding effects on the biogas quality in full‐scale anaerobic digestion by high resolution, photoacoustic‐based NDIR sensing. Issue 10 (20th August 2019) - Bierer, Benedikt; Kress, Philipp; Nägele, Hans‐Joachim; Lemmer, Andreas; Palzer, Stefan
Abstract: In future energy systems based on renewable energies, biogas plants can make a significant contribution to stabilizing the electricity grids. However, this requires load‐flexible and demand‐oriented electricity production by means of flexible feed management. However, these flexible feeding strategies using greatly oscillating, temporally varying high mass loads may lead to critical process failures of the anaerobic digestion process. Currently there is no online, high resolution gas quality measurement technique to detect and prevent biological process failures available. In this contribution, we present a miniaturized, low‐cost biogas quality measurement system providing data with high precision and high temporal resolution to overcome this technology gap. To highlight the capabilities of the system we have installed it using a bypass to the main biogas duct after hydrogen sulfide removal at a full‐scale research biogas plant. During a three‐month field trial, the effect of flexible feeding on the biogas quality has been monitored. The results demonstrate long‐term stability of the sensor solution and reveal the effects of changing feeding frequency and composition on gas quantity and quality, which cannot be detected with commercially available state‐of‐the‐art sensing systems.